Valvular imaging in the era of feature‐tracking: A slice‐following cardiac MR sequence to measure mitral flow - Seemann, F; Heiberg, E; Carlsson, M; Gonzales, RA; Baldassarre, LA; Qiu, M; Peters, DC (Wiley, 2019)
Background In mitral valve dysfunction, noninvasive measurement of transmitral blood flow is an important clinical examination. Flow imaging of the mitral valve, however, is challenging, since it moves in and out of the image plane during the cardiac cycle.